Cutaneous and systemic manifestations of EGFR inhibitor therapy: A case of PRIDE syndrome - Fadi Ali Alghamdi; Yaser Omar Alotaibi; Sumayah Dhafer Alshehri; Anhar Khalid Zahrani; Waseem Khalid Alhawsawi; Reema Saeed Alzaidi; Mohammed Fuad Bondagji; Ahmed Abdulshakur Niyazi (Journal of Family Medicine and Primary Care)
EGFR inhibitors have revolutionized the treatment of advanced malignancies by targeting cancer cells specifically. The “PRIDE” complex encompasses a range of cutaneous adverse effects linked to EGFR inhibition therapy, including acneiform eruptions, xerosis, eczema, paronychia, and hair and nail changes. Cutaneous toxicities are among the most reported adverse events in this context. This report presents a case illustrating the dermatological side effects of EGFR inhibition therapy. The case involves a 73-year-old man with colon cancer undergoing (folinic acid, fluorouracil, irinotecan) + cetuximab treatment, presenting with diffuse rash, severe xerosis, bilateral scleral congestion, hyperpigmentation, nail changes, abdomen and toe ulcers, and skin infections.